Tributo ao Prof. Helvécio Pereira de Castro - da Silva, Rosângela Maria; Alves Garcia, Ronaldo (NEXUS Mathematicæ, 2023)
Nesse trabalho descrevemos a trajetória acadêmica do Prof. Helvécio Pereira de Castro (1960-2021) na UFG.